2013
DOI: 10.1055/s-0033-1355164
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Efficacy of Prophylactic Enteral and Parenteral Nimodipine Treatment in Vestibular Schwannoma Surgery: A Comparative Study

Abstract: These results support a dependency of nimodipine's neuroprotective efficacy on its serum levels. Parenteral nimodipine treatment produces higher serum levels and has a higher neuroprotective potency in vestibular schwannoma surgery compared with enteral treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…Significance shows that this is not due to chance. The concentration-dependent potency of nimodipine was also seen in clinical trials, where detectibly higher nimodipine concentrations in the blood serum of patients correlated with better clinical outcomes [28]. …”
Section: Discussionmentioning
confidence: 99%
“…Significance shows that this is not due to chance. The concentration-dependent potency of nimodipine was also seen in clinical trials, where detectibly higher nimodipine concentrations in the blood serum of patients correlated with better clinical outcomes [28]. …”
Section: Discussionmentioning
confidence: 99%
“…Dies wird möglicherweise durch die perioperative Gabe von Nimodipin begünstigt. Es gibt Hinweise, dass Nimodipin neuroprotektive Eigenschaften besitzt und einen positiven Einfluss auf die Myelinisierung zu haben scheint [6,8].…”
Section: Diskussionunclassified
“…Herzfeld et al demonstrated a reduction of apoptosis in nimodipine-treated neuro2a cells via surgery-like stress models [4,5]. Several monocenter, retro-and prospective clinical trials pointed to a beneficial effect of nimodipine on the long-term outcome of cranial nerve functions following VS surgery [7][8][9][10][11][12][13][14]. A monocentric pilot study on 30 subjects showed a superiority of its prophylactic administration compared to an intraoperative start or no treatment [9].…”
mentioning
confidence: 99%